Impact of ship operations aided by voyage optimization on a ship’s fatigue assessment - Lang, Xiao; Wang, Helong; Mao, Wengang; Osawa, Naoki (Journal of Marine Science and Technology, 2021)
In this study, different operation factors affecting a ship’s wave statistics are studied, such as the slow steaming and voyage optimizations. Especially, the impact of various voyage optimization methods on the long-term wave statistics and corresponding fatigue damage during ship operations is investigated by comparing the encountered waves with the design wave scatter diagram. Three years of full-scale measurements from a container ship sailing in the North Atlantic are employed to study the impact, in addition to noon reports from two fleets of container ships and VLCCs. Furthermore, the benefits of using voyage optimizations for minimum fatigue damage accumulation during operation are discussed. The large difference of wave statistics is found when the ship follows routes generated by various optimization methods and the design diagram. For some westbound voyages, the voyage optimization methods can significantly decrease the ship’s fatigue damage accumulations, leading to longer fatigue life.